Low Molecular Weight Z-Tetraol Boundary Lubricant Films in Hard Disk Drives. (3rd December 2012) - Waltman, R. J.; Deng, H.
Abstract : Lower molecular weight Z-Tetraol films exhibit increased mechanical spacing in the slider-disk interface due to a lower z-profile. An increased resistance to lubricant disturbance on the disk surface (e.g., lube moguls) with decreasing film thickness is attributed to an increasing contribution from the polar component of the disjoining pressure. Evaporative loss at temperatures typically encountered in a hard-disk drive also increases with decreasing molecular weight but is strongly dependent on the initial bonded fraction.